2011
DOI: 10.1016/j.wocn.2010.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of exposure frequency in recognizing pronunciation variants

Abstract: Words can be pronounced in multiple ways in casual speech. Corpus analyses of the frequency with which these pronunciation variants occur (e.g., Patterson & Connine, 2001) show that typically, one pronunciation variant tends to predominate; this raises the question of whether variant recognition is aligned with exposure frequency. We explored this issue in words containing one of four phonological contexts, each of which favors one of four surface realizations of word-medial /t/: [t], [ʔ], [ɾ], or a deleted va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
31
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 23 publications
8
31
3
Order By: Relevance
“…In our study, we similarly did not find any facilitation of word recognition when listeners heard glottalized [ʔ͡ t] compared to non-glottalized [t]. These results are consistent with the robust finding that canonical forms are privileged, despite their actual production frequency across contexts (McLennan et al, 2003(McLennan et al, , 2005Ranbom & Connine, 2007;Pitt, 2009;Pitt et al, 2011;Ranbom et al, 2009;Tucker, 2011). It is an open question, however, how much of a perceptual mismatch glottalized voiced stops are.…”
Section: Glottalization As Phonetic Enhancement and Phonological Varisupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, we similarly did not find any facilitation of word recognition when listeners heard glottalized [ʔ͡ t] compared to non-glottalized [t]. These results are consistent with the robust finding that canonical forms are privileged, despite their actual production frequency across contexts (McLennan et al, 2003(McLennan et al, , 2005Ranbom & Connine, 2007;Pitt, 2009;Pitt et al, 2011;Ranbom et al, 2009;Tucker, 2011). It is an open question, however, how much of a perceptual mismatch glottalized voiced stops are.…”
Section: Glottalization As Phonetic Enhancement and Phonological Varisupporting
confidence: 90%
“…Several researchers have examined listeners' ability to recognize familiar words produced with a glottal variant of /t/ both in word-medial (Pitt et al, 2011) as well as in word-final coda position (Sumner & Samuel, 2005). In particular, word-final glottal variants of /t/ (both [ʔ͡ t or ʔ]) were as effective as canonical non-glottalized [t] at priming a semantically-related target.…”
Section: Perception Of Phonological Variants and Coarticulationmentioning
confidence: 99%
“…First of all, there is evidence that adults store representations of reduced pronunciation variants in their mental lexicons (Bürki et al, 2010;Pitt et al, 2011;Ranbom and Connine, 2007). Given the high frequency of reduced pronunciation variants in our data, it could well be the case that these representations are acquired in infancy.…”
Section: Discussionmentioning
confidence: 70%
“…They showed that the relative frequencies of the pronunciation variants are correlated with response latencies: participants produced a variant faster the more frequent it is relative to the other variant. Finally, Pitt, Dilley and Tat (2011) investigated the correlation between the frequencies of different pronunciation variants of word-medial /t/ in American English ([t], [ʔ], [ɾ] and a deleted variant) and recognition in a lexical decision task. They found that the more commonly produced variants are also more easily recognized.…”
mentioning
confidence: 99%
“…Such episodic storage, however, does not make prelexical reconstruction superfluous. It has been repeatedly found that, compared to reduced forms, canonical forms have an advantage in speech comprehension (e.g., Ernestus, 2009;Pitt, Dilley, & Tat, 2011). Adapting to a given speaker's reduction style via prelexical reconstruction would allow listeners to access canonical forms, which would in turn facilitate recognition.…”
Section: Discussionmentioning
confidence: 99%